Supraventricular tachycardia induced by central venous catheter in a newborn - Portela, Mariana; Leite, Lídia; Granja, Sofia; Raposo, Filipa; Barroso, Almerinda; Machado, Clara (BIRTH AND GROWTH MEDICAL JOURNAL, 2022)
Introduction: Central venous catheter (CVC) is an important tool in newborn care in the Neonatal Intensive Care Unit. Complications related to CVC placement, such as tachyarrhythmia, are most often due to malposition. Case report: Herein is reported the case of a preterm neonate who developed supraventricular tachycardia after insertion of an umbilical venous catheter (UVC). The UVC was pulled out, but reestablishment of the sinus rhythm required adenosine administration. Discussion: Despite being rare in preterm newborns, tachyarrhythmia is a well-known complication of catheter malposition, mostly caused by low anatomic accuracy associated with the small size of the heart. Conclusion: In cases of tachyarrhythmia in newborns, it is mandatory not only to review the CVC position within the heart but also to rapidly diagnose the type of arrhythmia, avoiding more severe complications.